Using the Plotagon Application on Arabic Language Learning Media Design - Rini, Rini; Mustofa, Muhammad Arif; Kurnia, Kurnia (Institut Agama Islam Negeri Curup, 2023)
This article aimed to describe the results of research related to the design of Arabic language learning media using the Plotagon application, as an alternative interactive Arabic learning media which was still very lacking. The research was conducted using research and development (R&D) with the Borg & Gall Model development model. The research results showed that based on the validation results of the Arabic language learning media using the Plotagon application by material experts, which included learning aspects and material content aspects, an average score of 4.62 (very good) was obtained with feasibility test results of 92.5%. Meanwhile, the assessment from media experts, encompassing appearance aspects and programming aspects, obtained an average score of 4.70 (very good) with a feasibility result of 94.19%. Consequently, the Arabic language learning media based on the Plotagon application proved to be suitable for use. The utilization of Plotagon animation in learning speaking skills made it easier for students to comprehend the material and increased studentsâ€™ enthusiasm and motivation. Based on the results of data processing, it was evident that the developed Plotagon animation could be used in the learning process.Â